2021
DOI: 10.1155/2021/9978409
|View full text |Cite
|
Sign up to set email alerts
|

Random Forest versus Support Vector Machine Models’ Applicability for Predicting Beam Shear Strength

Abstract: The shear and bending are the actions that are experienced in the beam owing to the fact that the beam is a flexural member due to the load in the transverse direction to their longitudinal axis. The shear strength (Vs) computation of reinforced concrete (RC) beams has been a major topic in the field of structural engineering. There have been several methodologies introduced for the Vs prediction; however, the modeling accuracy is relatively low owing to the complex characteristic of the resistance mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…This suggests that the relationship between soil color and SOM can be more easily explained with the RF algorithm, which has the capacity to capture nonlinear relationship. A previous study yielded similar outcomes to our research, including the superior performance of the RF algorithm compared to the SVM algorithm and the observation that R 2 values decreased when applied to the test dataset as opposed to the training dataset (Mohammed & Ismail, 2021). Furthermore, several studies by Mahmoudzadeh et al.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This suggests that the relationship between soil color and SOM can be more easily explained with the RF algorithm, which has the capacity to capture nonlinear relationship. A previous study yielded similar outcomes to our research, including the superior performance of the RF algorithm compared to the SVM algorithm and the observation that R 2 values decreased when applied to the test dataset as opposed to the training dataset (Mohammed & Ismail, 2021). Furthermore, several studies by Mahmoudzadeh et al.…”
Section: Resultssupporting
confidence: 85%
“…This suggests that the relationship between soil color and SOM can be more easily explained with the RF algorithm, which has the capacity to capture nonlinear relationship. A previous study yielded similar outcomes to our research, including the superior performance of the RF algorithm compared to the SVM algorithm and the observation that R 2 values decreased when applied to the test dataset as opposed to the training dataset (Mohammed & Ismail, 2021). Furthermore, several studies by Mahmoudzadeh et al (2020), Tziachris et al (2019), andZhang et al (2021) have demonstrated that when predicting the SOM content, the RF algorithm consistently outperforms other algorithms such as SVM, cubist, ordinary kriging, regression kriging, gradient boosting, decision tree, and bagging decision tree.…”
Section: Accurate Som Prediction Observed In the Rf-based Predictive ...supporting
confidence: 85%
“…In total, 118 experimental observations were used, and the trained model could successfully simulate the effects of input variables on the shear capacity of RC beams without stirrups. Moving away from ANNs, Mohammed and Ismail (2021) predicted the shear capacity of RC beams using a random forest (RF). The data they used comprised 349 experimental samples, and they validated the prediction by comparing it to the results of a support vector machine (SVM) and other empirical equations.…”
Section: Machine Learning Approachesmentioning
confidence: 99%
“…Owing to its exceptional performance, RF was extensively employed in predicting the mechanical properties of reinforced concrete (RC) in construction engineering [37][38][39][40][41]. Mohammed et al [42] compared the performance of support vector machines (SVM) and RF models for predicting the shear strength of RC beams and found that the RF model has a better prediction accuracy than the SVM model. Zhang et al [32] compared the prediction performance of the BPNN and RF models for estimating the shear strength of RC beams with and without stirrups.…”
Section: Introductionmentioning
confidence: 99%